The Relationship between Critical Thinking Skills and Biology Creative Thinking Skills for High School Students in the Think Pair Share (TPS) Learning Model - Fandi Tri Fajar Cahyo; Herawati Susilo; Sulisetijono Sulisetijono (Jurnal Pendidikan Sains, 2021)
Abstract: Critical thinking enables students to process information logically, creative thinking brings out imaginative ideas. Both can be empowered by applying the Think Pair Share (TPS). This research is a quasi-experimental design involving students of grade 10 and 11 SMAN 9 Malang. Aspects of critical and creative thinking skills are measured using essay tests. To show the relationship between critical and creative thinking skills and the contribution, regression analysis was carried out. The results showed that there was a significant relationship between critical and creative thinking.Abstrak: Berpikir kritis memungkinkan siswa untuk memproses informasi secara logis, sedangkan berpikir kreatif memunculkan ide yang imajinatif. Kedua berpikir kritis dan kreatif dapat diberdayakan dengan menerapkan model pembelajaran Think Pair Share(TPS). Penelitian ini merupakan kuasi eksperimen pada siswa kelas 10 dan 11 SMAN 9 Malang. Aspek berpikir kritis dan berpikir kreatif diukur menggunakan soal tes essay. Untuk mengungkap hubungan berpikir kritis dan kreatif dan besar sumbangan, dilakukan analisis regresi. Hasil menunjukkan terdapat hubungan signifikan antara berpikir kritis dan berpikir kreatif.